2011
DOI: 10.1177/0037549711416244
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating electronic health record systems: a system dynamics simulation

Abstract: Implementing electronic health record (EHR) systems in the next few years is on the agenda for many healthcare organizations. Before investing in an EHR system, however, decision makers need to identify and measure the benefits of such systems. We propose using a system dynamics (SD) approach to measuring the benefits of EHR systems. Using an SD approach, it is possible to map complex relationships among clinical processes in hospitals into a model by which one can dynamically measure the effect of any changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Benefits of internet use to patients include; more informed patients, ability of patients to seek second opinions, patients joining online communities for support, patients being able to communicate online with health care providers, supplementing information provided by health care providers and improving conceptualization of information gained, patients enjoy more privacy than face to face consultations [11,14-17]. The health care providers would benefit from decision making tools, time efficiency and cost containment [18]. Investment in e-health may result in overwhelming technological, financial and informational demands on the clients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benefits of internet use to patients include; more informed patients, ability of patients to seek second opinions, patients joining online communities for support, patients being able to communicate online with health care providers, supplementing information provided by health care providers and improving conceptualization of information gained, patients enjoy more privacy than face to face consultations [11,14-17]. The health care providers would benefit from decision making tools, time efficiency and cost containment [18]. Investment in e-health may result in overwhelming technological, financial and informational demands on the clients.…”
Section: Introductionmentioning
confidence: 99%
“…Even though many websites containing cancer information are available, much of the information contained in these websites may lack quality [16]. Lack of information on the other hand may increase anxiety among patients as well as hinder their health seeking behaviours [18,19]. It is important to study the characteristics of patients who use internet as a source of health information.…”
Section: Introductionmentioning
confidence: 99%
“…This is also in confirmation of the work of McCullough, et al, Hydari et al, and Furukawa et al among others. [3,12,13] Overwhelming number of medical practitioners confirmed that EHR promotes quality of medical care as well as reduces the rate of medical errors and PSEs in the hospital. [4,12,13] This is in concord with Hydari et al study with the result of a 27% overall decline in PSEs in hospitals that adopted and implemented EHR.…”
Section: Discussionmentioning
confidence: 99%
“…[3,12,13] Overwhelming number of medical practitioners confirmed that EHR promotes quality of medical care as well as reduces the rate of medical errors and PSEs in the hospital. [4,12,13] This is in concord with Hydari et al study with the result of a 27% overall decline in PSEs in hospitals that adopted and implemented EHR. [3] This feat was achieved by EHR through improved communication, better labeling, clear writing, bridging of knowledge gaps, and timely provision of patients' medical records as well as improved physician's confidence.…”
Section: Discussionmentioning
confidence: 99%
“…They developed an economic justification for investment in laboratories, diagnostic facilities, and physicians and suggested additional equipment for an emergency department. Kasiri and colleagues () studied the dynamics of an electronic health record system to reduce the time spent by the staff, showing that their conceptual record system balanced staff time and resulted in greater cost efficiency for hospitals. SD has also been used by modelers to create forecasts for future resource problems.…”
Section: Literature Reviewmentioning
confidence: 99%